Сrohn's disease with skin lesions in the form of gangrenous pyoderma (clinical case) - L. V. Tarasova; E. I. Busalaeva (Лечащий Врач)
Diagnosis of Crohn's disease is a complex, often lengthy process, which is based on a consistent differential diagnostic search. A significant proportion of patients with Crohn's disease may develop extraintestinal manifestations. Often, skin lesions precede the manifestation of intestinal symptoms or occur in parallel with intestinal manifestations. Their spectrum is quite wide, and the mechanism of occurrence is heterogeneous. In particular, autoimmune extraintestinal manifestations associated with the activity of the inflammatory process are isolated, which appear along with the main intestinal symptoms of exacerbation and, with the modern appointment of adequate pathogenetic therapy, are resolved in parallel with a decrease in the degree of activity of intestinal inflammation. Skin lesions in inflammatory bowel diseases, according to various authors, occur in 6-43% of cases. Skin changes in inflammatory bowel diseases are explained by common pathogenetic mechanisms: hyperproduction of IL-12 and interferon-gamma synthesized by Th1-lymphocytes, IL-5 and IL-13 produced by Th2-lymphocytes, IL-17 by Th17-lymphocytes. One of the severe skin lesions in Crohn's disease is pyoderma gangrenosum, an inflammatory neutrophilic dermatosis characterized by painful ulcerative skin defects (ulcers of polycyclic outlines with raised edges and covered with necrotic masses) and often associated with diseases of the internal organs. The article describes a clinical case of a patient with Crohn's disease and pyoderma gangrenosum. The stages of differential diagnostic search and treatment are described. The interleukin 12/23 inhibitor ustekinumab has been shown to be highly effective in achieving clinical, laboratory and endoscopic effects already at early stages of treatment. At the same time, in parallel with the healing of the mucosa of the terminal ileum, skin manifestations were also reduced. This clinical case also confirms the importance of such factors as the severity of the course of the disease and the presence of extraintestinal manifestations when choosing the first biological drug for the treatment of Crohn's disease.